Anti-Cocaine Vaccine Based on Coupling a Cocaine Analog to a Disrupted Adenovirus - Koob, George; J. Hicks, Martin; Wee, Sunmee; B. Rosenberg, Jonathan; P. De, Bishnu; M. Kaminksy, Stephen; Moreno, Amira; D. Janda, Kim; G. Crystal, Ronald (CNS & Neurological Disorders - Drug Targets, 2011)
The challenge in developing an anti-cocaine vaccine is that cocaine is a small molecule, invisible to the immune system. Leveraging the knowledge that adenovirus (Ad) capsid proteins are highly immunogenic in humans, we hypothesized that linking a cocaine hapten to Ad capsid proteins would elicit high-affinity, high-titer antibodies against cocaine, sufficient to sequester systemically administered cocaine and prevent access to the brain, thus suppressing cocaine-induced behaviors. Based on these concepts, we developed dAd5GNE, a disrupted E1-E3- serotype 5 Ad with GNE, a stable cocaine analog, covalently linked to the Ad capsid proteins. In pre-clinical studies, dAd5GNE evoked persistent, high titer, high affinity IgG anti-cocaine antibodies, and was highly effective in blocking cocaine-induced hyperactivity and cocaine self-administration behavior in rats. Future studies will be designed to expand the efficacy studies, carry out relevant toxicology studies, and test dAd5GNE in human cocaine addicts.
Keywords: Laser evoked potential